2022
DOI: 10.1093/jme/tjac113
|View full text |Cite
|
Sign up to set email alerts
|

Spatiotemporal Environmental Drivers of Eastern Equine Encephalitis Virus in Central Florida: Towards a Predictive Model for a Lethal Disease

Abstract: Eastern equine encephalitis virus (EEEV) is a mosquito-borne virus that affects humans and horses, with a high case fatality rate in both species. The virus can be transmitted by several mosquito species and maintained in multiple reservoir hosts, making EEEV dynamics difficult to anticipate. In this study, we identified spatial and temporal factors that precede EEEV detection using sentinel chicken surveillance data from Orange County, Florida, from 2003 to 2017. We first examined the land cover and mosquito … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 42 publications
0
1
0
Order By: Relevance
“…In addition to the effect of urban landscapes, I found that forested land cover was positively associated with EEEV seroprevalence in Song Sparrows, and negatively associated with WNV seroprevalence. For EEEV virus, this is consistent with the importance of forested wetland areas to the main vectors of EEEV, notably Culiseta melanura (167)(168)(169)(170). In Eastern Ontario, Culex pipiens/restuans mosquitoes are less prevalent in forests (171), which explains my observation that WNV seroprevalence in Song Sparrows was lower in forested land covers.…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…In addition to the effect of urban landscapes, I found that forested land cover was positively associated with EEEV seroprevalence in Song Sparrows, and negatively associated with WNV seroprevalence. For EEEV virus, this is consistent with the importance of forested wetland areas to the main vectors of EEEV, notably Culiseta melanura (167)(168)(169)(170). In Eastern Ontario, Culex pipiens/restuans mosquitoes are less prevalent in forests (171), which explains my observation that WNV seroprevalence in Song Sparrows was lower in forested land covers.…”
Section: Discussionsupporting
confidence: 75%
“…For EEEV however, studies investigating a relationship between human landscapes and disease risk are scarce. This is likely a consequence of an established relationship between EEEV prevalence, its primary mosquito vector Culiseta melanura (59), and forested wetland habitats (167)(168)(169)(170). However, mosquitoes involved in EEEV transmission, most notably Culiseta melanura, are still found in urban and agroecosystems (171) that may include patches of forest and wetlands used by these mosquitoes (172,173).…”
Section: Introductionmentioning
confidence: 99%
“…melanura has also been found to occasionally feed on mammals in the Northeast (Molaei et al, 2006). In terms of viral dynamics, previous work demonstrated that EEEV circulates year round in Florida and is introduced into the Northeast through seasonal bird migration (Mundis et al, 2022;Tan et al, 2018), although this process does not happen predictably every year. Predicting the annual case dynamics is therefore difficult, having to take into account viral dynamics across multiple species and geographic scales.…”
Section: Introductionmentioning
confidence: 99%